Field emission studies of novel ZnO nanostructures in high and low field regions - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S.; Pillai, Vijayamohanan K. (Nanotechnology, 2006)
A study of the field emission characteristics of novel structures of ZnO, namely marigolds, multipods and microbelts, has been carried out in both the close proximity configuration and the conventional field emission microscope. The use of a conventional field emission microscope overcomes the drawback of arc formation at high field values. The nonlinearity in the Fowler - Nordheim ( F - N) plot, a characteristic feature of semiconductors has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability exhibited by these structures is also promising for future device applications.

ZnO multipods, submicron wires, and spherical structures and their unique field emission behavior - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; More, Mahendra A.; Mulla, Imtiaz S.; Joag, Dilip S.; Vijayamohanan, K. (Journal of Physical Chemistry B, 2006)
A simple method of vapor deposition for the shape selective synthesis of ZnO structures, namely, multipods, submicron wires, and spheres, has been successfully demonstrated. A plausible growth mechanism based on the studies of scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) is proposed. Our studies suggest that the growth of a multipod structure is governed by the screw dislocation propagation while the vapor-liquid-solid (VLS) mechanism is responsible for the formation of submicron wires and spheres. Moreover, the flow rate of the carrier gas plays a crucial role in governing the morphology. Further, these structures exhibit an enhanced field emission behavior. The nonlinearity in the Fowler-Nordheim (F-N) plot, a characteristic feature of electron emission from semiconductors, is explained by considering the contributions from both the conduction and the valence bands of ZnO.

Energy analysis of field emitted electrons from a ZnO tetrapod - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Ramgir, Niranjan S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Applied Physics Letters, 2007)
The experimental total energy distribution (TED) of the field emitted electrons from a single pod of a ZnO tetrapod has been obtained, exhibiting a two-peak feature. The energy difference between the two peaks in the TED is found to be nearly equal to the band gap of the bulk ZnO. The results show that field emitted electrons originate from both the conduction and valence bands. The peak position dependence on the applied voltage has also been observed. In the present case, the size of the ZnO tetrapod is not small enough to reflect the quantum confinement effects.

Field emission investigations of RuO2-doped SnO2 wires - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Applied Surface Science, 2007)
Field emission studies of a bunch and a single isolated RuO2:SnO2 wire have been performed. A current density of 5.73 x 10(4) A/cm(2) is drawn from the single wire emitter at an applied field of 8.46 x 10(4) V/mu m. Nonlinearity in the Fowler-Nordheim (F-N) plot has been observed and explained on the basis of electron emission from both the conduction and the valence bands of the semiconductor. The current stability recorded at the preset value of 1.5 LA is observed to be good. Overall the high emission current density, good stability and mechanically robust nature of the RuO2:SnO2 wires offer advantages as field emitters for many potential applications. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emission; field enhancement factor; RuO2; SnO2

Surface-state-mediated electron transfer at nanostructured ZnO multipod/electrolyte interfaces - Parthasarathy, Meera; Ramgir, Niranjan S.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
Redox kinetics of cyanoferrate(III) species adsorbed at an n-type ZnO multipod/electrolyte interface is explored using electrochemical techniques like cyclic voltammetry and impedance spectroscopy. The electrochemical impedance results are analyzed using a fluctuating energy level model, assuming isoenergetic tunneling of majority carriers through the Helmholtz layer. A shift in the slope of Mott-Schottky plots (C-sc(-2) versus E) together with evidence from cyclic voltammetry shows that the electron-transfer process is mediated by surface states formed because of the adsorption of ferricyanide ions (as evident from the results of Fourier transform infrared spectroscopy). More significantly, the pH of zero charge (point of zero zeta potential, pzzp) of ZnO multipods is found to be 4.5 (from capacitance vs pH plots) compared to that of bulk ZnO (pH 9.5), which could be explained on the basis of a lowering in the work function of the nanostructured semiconductor and its consequent susceptibility to the formation of surface states. This is in excellent agreement with our earlier observation of ultralow threshold field emission with this material in the light of the linear dependence of pzzp with work function of the electrode material. The flat-band potential of the nanostructures is found to be 200 mV more negative than that reported for bulk n-type ZnO electrodes, indicating a higher doping density in the former. A three-dimensional mapping of charge distribution in the surface states is attempted by correlating the capacitance response of the system subjected to a sinusoidal potential modulation to the semiconductor electrode with that resulting from a systematic variation of the redox potential of the dissolved acceptor (achieved by varying the pH of the electrolyte) which further reveals the polyenergetic nature of the surface states.

RuO(2) doped SnO(2) nanobipyramids on Si (100) as a field emitter - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Thin Solid Films, 2008)
Thin films of RuO(2): SnO(2) nanobipyramids have been grown on silicon (100) flat substrates, and their field emission behavior has been investigated. The field emission experiments have been performed in parallel plate configuration. In this experiment, the onset field for 0. 1 gA/ cm 2 current density has been found to be 0.2 V/mu m. The Fowler-Nordheim plot shows non-linear nature typical that of a semiconductor. The field enhancement factor has been estimated to be 35,600 cm(-1), indicating that the field emission originates from the nanometric features of the emitter. The current stability recorded at a preset value of I tA is observed to be good. Our field emission results on RuO(2): SnO(2) nanobipyramids indicate that, RuO(2): SnO(2) nanobipyramids are a potential candidate for futuristic field emission based devices. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emitter; field enhancement factor; ruthenium oxide; tin oxide